Continuous Progressive Actuator Robot for Hand Rehabilitation - Ying, S. Z.; Al-Shammari, N. K.; Faudzi, A. A.; Sabzehmeidani, Y. (Engineering, Technology & Applied Science Research, 2020)
This paper presents the development of a soft rehabilitation robot to conduct Continuous Passive Motion (CPM) for hand rehabilitation. The main contribution of this work is the implementation of a McKibben actuator as an artificial muscle due to its proven advantages: simple structure, light weight, and high power-to-weight ratio. The development worked successfully when tested on a healthy subject, where the flexion and extension of the finger were controlled with an antagonistic pair of actuators. However, there is a limitation of the McKibben actuator regarding its length-dependency. In this research, the concept of a pulley system was proposed to overcome this limitation. Although there is a friction factor that reduces the contracting displacement by at least 15% of the original displacement, a pulley is still a potential solution as it can reduce the installation space of the actuator from 40 to 15cm while still producing sufficient force for the finger motion. Throughout this research, it was found that the pattern of the flexor pulley system is affecting the system’s efficiency in terms of motion assistance.